208k views
2 votes
Help me answer this question:/

Help me answer this question:/-example-1

1 Answer

1 vote

Answer:
(f\°g)(0)=3

Explanation:

- For the function g(x) you must find the value of y (output value) when
x=0. As you can see in the graph (observe the parabola), when
x=0 (input value), then:


y=2 or
g(0)=2

- Now, 2 will be the input value of the function f(x). Then, you must find the value of y (output value) when
x=2. As you can see in the graph of this function, when
x=2, then:


y=3 or
f(2)=3

Therefore, you can conclude that:


(f\°g)(0)=3

User Kate Orlova
by
5.6k points